2017
DOI: 10.1038/s41467-017-02315-4
|View full text |Cite
|
Sign up to set email alerts
|

The interhemispheric CA1 circuit governs rapid generalisation but not fear memory

Abstract: Encoding specificity theory predicts most effective recall by the original conditions at encoding, while generalization endows recall flexibly under circumstances which deviate from the originals. The CA1 regions have been implicated in memory and generalization but whether and which locally separated mechanisms are involved is not clear. We report here that fear memory is quickly formed, but generalization develops gradually over 24 h. Generalization but not fear memory is impaired by inhibiting ipsilateral (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 60 publications
2
35
2
Order By: Relevance
“…Here, we discovered that rapidly generalized memories do not require the vHPC, whereas remote generalized memories do, showing an opposite role of that of the dHPC. Thus, our data, in combination with recent findings (Lynch et al, 2017;Zhou et al, 2017), suggest that transformation of a specific fear memory into a generalized form may actually involve a shift in control over memory recall from the dHPC to the vHPC over time.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Here, we discovered that rapidly generalized memories do not require the vHPC, whereas remote generalized memories do, showing an opposite role of that of the dHPC. Thus, our data, in combination with recent findings (Lynch et al, 2017;Zhou et al, 2017), suggest that transformation of a specific fear memory into a generalized form may actually involve a shift in control over memory recall from the dHPC to the vHPC over time.…”
Section: Discussionsupporting
confidence: 76%
“…Although the ACC and HPC are implicated in anxiety disorders (see above citations) and generalized fear (Einarsson and Nader, 2012;Cullen et al, 2015;Zhou et al, 2017), little is known about the circuits through which they govern generalized fear responses. A single study found that circuits connecting the ACC and vHPC in the nucleus reunions are necessary for the learning of specific fear (Xu and Südhof, 2013), inactivating these circuits before training induces rapid fear generalization.…”
Section: Introductionmentioning
confidence: 99%
“…The encoding-retrieval exactly matched conditions lead to specific recall but these of partial matched ones result in generalization recall, according to the theoretical hypothesis “Toward a universal law of generalization for psychological science” ( Shepard, 1987 ). A recent report has demonstrated that rapid form of memory generalization is an active process to build up additional accesses to memory resources that allow fear to be transferred from one memory to another ( Zhou et al, 2017 ). Clinical study has suggested that MDD patients exhibit over generalization of negative memories ( Gotlib and Joormann, 2010 ).…”
Section: Evaluating Previous Effects Of Psychological Stressmentioning
confidence: 99%
“…Clinical study has suggested that MDD patients exhibit over generalization of negative memories ( Gotlib and Joormann, 2010 ). Therefore, according the rapid form of memory generalization, similar cues can retrieve negative emotion that links to old stress memories ( Zhou et al, 2017 ; Silva, 2017 ), possibly leading to automatically negative thinking ( Beck et al, 1961 ). Furthermore, psychological stress memories would have been accumulated to shape the cognitive appraisal pattern in individuals ( Bower, 1981 ; Folkman et al, 1986 ).…”
Section: Evaluating Previous Effects Of Psychological Stressmentioning
confidence: 99%
See 1 more Smart Citation